PENGARUH OPERASIONAL PLTD PADA BANDAR UDARA SYAMSUDIN NOOR BANJARBARU AKIBAT PEMUTUSAN TENAGA LISTRIK OLEH PT. PLN DITINJAU DARI SEGI EKONOMI - Syarifil anwar; Ahmadil Amin (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2019)
With the growing age and increasingly sophisticated technology, it will automatically bring changes in human life. Which will also be more and more demands and needs that must be met by humans to balance these developments. One of them is human needs for electrical energy. To meet the increasing electricity needs and to prevent total power outages from occurring, Syamsudin Noor Banjarbaru Airport uses PLTD (Diesel Power Plant) as a power supply for the operation of Syamsudin Noor Airport.Payment of electricity bills at the Syamsudin Noor airport will increase by operating the PLTD at the time of termination of electricity by PT. (PLN). Every month the electricity account must be paid by Syamsudin Noor Airport, but if there is a power cut, the PLTD will operate, so that it will cause additional costs every month at Syamsudin Noor Airport. Additional fees at Syamsudin Noor Banjarbaru Airport in addition to paying electricity bills every month, plus the total operational cost of PLTD (diesel engine) of Rp.15,215,370 Keywords: PLTD (diesel engine), AC generator, total operational cost of PLTD (diesel engine).